On-Street Parking Utilization and Management Efficiency: A Case Study of Mahendranagar, Nepal - Khadka, Rabin Khadka; Bhatt, Toran Prasad; Joshi, Lokesh; Negi, Crimsan Singh; Ghimire, Prashidhika (Far Western Review, 2025)
This study investigates the escalating issue of on-street parking in Mahendranagar, Nepal, concentrating on five principal streets that encounter elevated traffic volumes and significant parking demand. Accelerated urban growth and a persistent increase in car ownership have exerted significant pressure on constrained roadside areas, leading to congestion, road encroachment, and operational traffic disputes. Efficient parking management is important for urban area such as Mahendranagar, as it facilitates effective and smooth public transportation operations and promotes the utilization of sustainable mobility alternatives. A three-day field observation survey was conducted to analyze parking behavior, peak demand hours, and space use along the designated routes. The data gathering encompassed methodical vehicle counts, computation of parking indices, and evaluation of adherence to current parking restrictions. The findings illustrate the significant overuse of on-street parking facilities. Parking indices attained 182.50% on Street 1 and 191.25% on Street 5, unequivocally indicating demand significantly beyond available capacity. Maximum parking activity occurred in the morning from 9:30 to11:30 AM and in the afternoon from 3:00 to 3:30 PM. During these peak periods, most of the street accommodated over 300 parked vehicles, despite an effective capacity of only 160 vehicles. These conditions show the increase traffic occupancy and cause traffic congestion and safety hazards. Additionally, the problem has become even worse because there has been a substantial increase in vehicle registrations, especially two-wheelers, which have gone up by more than 15,000 units in the last five years. To deal with the immediate effects, we need things like clearly marked parking areas, stricter enforcement, and specific changes to the design of the streets. Long-term growth of sustainable urban transportation will depend on changes to infrastructure, such as widening roads, building multi-level parking lots, and using vertical parking systems. Public participation and technology-assisted parking management will also be important.